Analysis of axial flux permanent magnet generator. Issue 4 (1st July 2019) - Gołębiowski, Lesław; Gołębiowski, Marek; Mazur, Damian; Smoleń, Andrzej
Abstract : Purpose: The purpose of this paper is to compare the methods of calculating the parameters of air-cored stator flux permanent magnet generator and to compare these results with the measurements of the designed and manufactured generator. The generator is to be designed for operation in a wind power plant. Design/methodology/approach: An analytical method and 2D and 3D finite element methods (FEMs) were used to calculate the parameters of the coreless permanent magnet axial generator. The analytical method and 2D FEM were applied to individual cross-sections through the air gap of the machine. After the design and construction of the generator and measuring station, the results of calculations and measurements were compared. Findings: The results of investigated calculation methods and measurements were found to be mutually compatible. Analytical methods and 2D FEM required proper interpretation of the results when comparing them with the 3D FEM. The results of the measurements and calculations showed the usefulness of the generator for operation in a wind power plant. Originality/value: Full comparison of results of 2D and 3D calculations with the results of the measurements on the machine model confirmed the usefulness of fast 2D methods for the analysis of coreless generators. The results differed by the effects of leakage inductance of windings' front connections. The application of an axial generator designed with the described methods in a wind turbine showed its proper operation.